2017
DOI: 10.1160/th16-10-0787
|View full text |Cite
|
Sign up to set email alerts
|

Patient values and preferences for antithrombotic therapy in atrial fibrillation

Abstract: 1) What are patients' AF and SPAF therapy values and preferences? 2) How are SPAF therapy values and preferences affected by patient factors? 3) How does conveying risk information affect SPAF therapy preferences? and 4) What is known about patient values and preferences regarding novel oral anticoagulants (NOACs) for SPAF? Twenty-five studies were included. Overall study quality was moderate. Severe stroke was associated with the greatest disutility among AF outcomes and most patients value the stroke prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…Views of patients should also be central to decision‐making around choice of oral anticoagulants. A systematic review of patients' values and preferences for DOACs versus warfarin generated heterogeneous findings, highlighting the need for focusing on patients' individual values and preferences . A further systematic review reported that stroke risk reduction and a moderate increase in the risk of bleeding were the most important attributes for patients when deciding between DOACs and warfarin .…”
Section: Discussionmentioning
confidence: 99%
“…Views of patients should also be central to decision‐making around choice of oral anticoagulants. A systematic review of patients' values and preferences for DOACs versus warfarin generated heterogeneous findings, highlighting the need for focusing on patients' individual values and preferences . A further systematic review reported that stroke risk reduction and a moderate increase in the risk of bleeding were the most important attributes for patients when deciding between DOACs and warfarin .…”
Section: Discussionmentioning
confidence: 99%
“…We assessed patients from the five European countries that have the largest population sizes, which resulted in an underrepresentation of Eastern and Northern Europe countries. We intentionally did not include attributes related to probability of stroke and bleeding in our attribute set because we were interested in the tradeoff between convenience attributes and feared they would be dominated by effectiveness and safety concerns, as was shown earlier [8,9], but it would be very interesting to study whether there are different classes of patients with regard to the trade-off between benefit, risk, and convenience.…”
Section: Limitationsmentioning
confidence: 99%
“…Several recent studies addressed preference for anticoagulant therapy in patients with AF. To most patients, reducing stroke and bleeding risk is most important [8,9], but most DOACs have similar benefit-risk profiles on a population level. DOACs differ mostly from VKAs in convenience attributes (e.g., intake frequency, regular coagulation monitoring, or drug/food interaction) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient perspectives are important, and most patients place great emphasis on stroke prevention although adherence to treatment efforts require emphasis and implementation 48,49 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%